Synthesis of Silver Nanoparticles from Malva parviflora Extract and Effect on Ecto-5'- Nucleotidase(5'-NT), ADA and AMPDA Enzymes in Sera of Patients with Arthrosclerosis (Baghdad Science Journal, 2025)
The present research included synthesis of silver nanoparticle from(1*10-3,1*10-4 and1*10-5) M aqueous AgNO3 solution through the extract of M.parviflora reducing agent. In the process of synthesizing silver nanoparticles we detected a rapid reduction of silver ions leading to the formation of stable crystalline silver nanoparticles in the solution.